Working together to promote and celebrate the diversity of nursing. (12th May 2022) - McMahon, Alex; Tranka, Sue
Abstract : This year has been particularly challenging for nurses around the world. As the commemorations take place for International Nurses Day on 12 May, the Chief Nursing Officer for Scotland and Chief Nursing Officer for Wales share their priorities and hopes for the coming year